2011
DOI: 10.3892/ijo.2011.1265
|View full text |Cite
|
Sign up to set email alerts
|

Newcastle disease virus induces pro-inflammatory conditions and type I interferon for counter-acting Treg activity

Abstract: Abstract. Newcastle disease virus (NDV) is a negative sense RNA paramyxovirus of birds which in human tumor cells, in contrast to human non-tumor cells, has shown replication competence leading to tumor cell death (i.e., tumor selectivity and viral oncolysis). Our study demonstrates that this virus induces high levels of pro-inflammatory cytokines in the bronchial lavage fluid of mice after nasal application and also in vitro in human dendritic cells (DCs). NDV is known as a very efficient inductor of type I i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…Notably, this effect was associated with relative reduction in the number of Tregs and marked enhancement of CD4 and CD8 effector to Treg ratios, which has been previously demonstrated to be a marker of a favorable immunological response to immunotherapy(29, 30). At present it is unclear what contributes to the relative reduction in the number of Tregs, although NDV-induced inflammatory cytokines have been previously suggested to have functions that could counter Treg activity (31). There is also a possibility that not all of the infiltrating FoxP3- CD4+ cells exhibit effector functions, as FoxP3- regulatory T cells have been previously reported (32).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, this effect was associated with relative reduction in the number of Tregs and marked enhancement of CD4 and CD8 effector to Treg ratios, which has been previously demonstrated to be a marker of a favorable immunological response to immunotherapy(29, 30). At present it is unclear what contributes to the relative reduction in the number of Tregs, although NDV-induced inflammatory cytokines have been previously suggested to have functions that could counter Treg activity (31). There is also a possibility that not all of the infiltrating FoxP3- CD4+ cells exhibit effector functions, as FoxP3- regulatory T cells have been previously reported (32).…”
Section: Discussionmentioning
confidence: 99%
“…Another study also demonstrated that genetically engineered NDV induced IFN-α and IFN-β in normal cells but only IFN-β in most tumor cells;28 in addition, IFN-α was shown to be expressed in mouse bronchoalveolar lavage (BAL) and mouse/human monocytes 29. Yet, there have been no reports demonstrating that IFN-λ is expressed higher than IFN-α/β in normal human cells after NDV infection.…”
Section: Resultsmentioning
confidence: 99%
“…Also, murine DCs upon infection by NDV differentiate into the immunogenic phenotype DC1 characterized by secretion of pro-inflammatory cytokines, in particular IL-12 and IFN-α and -β (44). Two receptor-initiated signaling cascades were involved: the first one is induced by triggering and upregulation of the intra-cellular cytoplasmic receptor RIG-1 upon recognition of viral non-capped RNA as ligand (45).…”
Section: Future Perspective: Combining Ndv With Bsabs and With Adoptimentioning
confidence: 99%
“…Two receptor-initiated signaling cascades were involved: the first one is induced by triggering and upregulation of the intra-cellular cytoplasmic receptor RIG-1 upon recognition of viral non-capped RNA as ligand (45). The second signal cascade involves cell-surface expressed type I IFN receptor (IFNAR), which initiates a feedback loop cell activation upon interaction with extra-cellular type I IFN as ligand (31, 44). RIG-1/RNA ligand interaction not only activates type I IFN, but also induces inflammasome activation for IL-1β production (46).…”
Section: Future Perspective: Combining Ndv With Bsabs and With Adoptimentioning
confidence: 99%